Successful freelancing for web designers : the best of smashing magazine - Smashing Magazine (Chichester, West Sussex, U. K. : Wiley, 2011)
"True to the Smashing Magazine?s promise, Successful Freelancing for Web Designers: The Best of Smashing Magazine smashes readers with the information they need to make their life easier. Really. Being a great Web designer or developer is one thing - running a successful freelance business another. Whether you already have work experience in companies or have just graduated from design school, being self-employed entails a number of tasks that you most likely haven?t had to deal with so far. Written by some of the best in the business, this book incorporates some of the very best of Smashing Magazine?s features on working as a freelance web professional. Basic Skills of Freelance Web Designers. Essential Habits of An Effective Professional Freelancer. Common Questions of Web Designers. The Designer Who Delivers. Critical Mistakes Freelancers Make. The Importance of Customer Service. Creatively Handling the Admin Side of Freelancing. Pitching Like a Pro. The Finances of Freelancing Communication with Clients & Partners. How To Identify and Deal With Different Types Of Clients. 5 Simple Tips for Improving Designer-Client Relationships. How to Communicate with Developers Effectively. How to Educate Your Clients on Web Development. How to Explain to Clients that They Are Wrong. How to Respond Effectively to Design Criticism. How to Persuade Your Users, Boss or Clients. How to Create the Perfect Client Questionnaire. Marketing - Convincing Strategies for Freelancers. Getting Clients: Approaching the Company. Converting Prospects into Clients. Marketing Rules and Principles for Freelancers. How Many Ideas Do You Show Your Clients? Contracts & Pricing. Freelance Contracts: Do?s And Don?t?s. What?s In A Price: Guidelines For Pricing Web Designs. Quality-Price-Ratio in Web Design"-- Provided by publisher.
1. Basic skills of freelance web designers -- 2. Communication with clients and partners -- 3. Marketing: effective strategies for freelancers -- 4. Contracts and pricing
Includes index
Keywords: New business enterprises; Self-employed; Web site development industry; Web sites -- Design -- Marketing